Propuesta de intervención en estrategias de inteligencia emocional para los problemas conductuales de los usuarios con discapacidad intelectual de la Unidad Básica de Rehabilitación Municipal del cantón Puyango provincia de Loja, período octubre 2020-marzo 2021 - Aguilar Ullaguari, Silvania del Cisne (2021)
People with intellectual disabilities require the control and regulation of emotions, therefore, an intervention proposal was established in emotional intelligence strategies for the behavioral problems of users with intellectual disabilities of the Basic Municipal Rehabilitation Unit of the Puyango canton, Loja province , which aimed to determine strategies to strengthen emotional intelligence in the behavioral problems of users with intellectual disabilities, which was carried out in a sample of 6 users aged 8 to 16 years. The research corresponding to a descriptive, explanatory, analytical, quantitative and qualitative approach was used the scientific, inductive - deductive, analytical - synthetic, statistical and descriptive method, the Test of TIEN and SDQ-Cas obtaining as a result a moderate level of emotional intelligence, with difficulties mainly in the dimensions of self-control, social ability and self-motivation with problems in the components of emotional symptoms, behavioral problems and hyperactivity scale. After the intervention proposal, the post-test was applied, giving satisfactory results, thus concluding the implementation of the workshops and manual for the strengthening of EI and behavioral management for users of users with intellectual disabilities. regulation, control of emotions and behavior management